Candy crushing your sleep - JEYARAJAH, Kasthuri (Institutional Knowledge at Singapore Management University, 2015)
Growing interest in quantified self has led to the popularity of lifelogging applications. In particular, health and wellness related applications have seen an upsurge with the advent of wearables such as the Fitbit. In this paper, we focus on the quality of sleep that directly impacts the overall wellness of individuals. In particular, in this work, we present a first of its kind study that (1) unobtrusively quantifies the quality of sleep and (2) seeks to identify attributing aspects of our daily lives such as an individual's usage of apps throughout the day and his/her physical environment that may affect sleep. We use real life, in-situ smartphone data from 400+ undergraduate students over an observation period of 15 months, and present our initial observations.